Optimisation of percutaneus coronary intervention with optical coherence tomography - Perišić, Zoran; Lazarevic, Mihajlo (Acta medicae Medianae, 2021)
Introduction: Optical coherence tomography(OCT) is a method which provides precise insight of morfology of coronary arteries. Appliance of OCT can evaluate atherosclerotic plauqes, stoutness of fibrous cap, and also gives precise illustration of stent possition in coronary artery. Case outline: 72 year old woman was received with acute myocardial infarction with ST segment elevation in anterolateral leads, and immediatelly was sent to catheterization lab to PCI. During the procedure we found occluded left circumflex artery, and after predilatation, two stents was implanted. Flow rate of stents was very slow, and signs of stents thrombosis were registrated. The flow rate neither renovate after postdilatation and thrombus aspiration. The consequence of patients rapid collapse condition, the procedure was adjourn, and we continuous therapy with GP inhibitors, anticoagulant and antithrombotic therapy. After 7 days coronary angiography was repeated, and OCT system was used. We found substantionally aposition of stent where some struts were distant to 0.5mm from wall of coronary artery. The postdilatation was done with larger ballon by measured artery diameter, afterwards the thrombosis disapears and struts near the wall of coronary artery. The patients was discharge from hospital with dual antiplatelet therapy in a good condition. Conclusion: OCT is new diagnostic method which provides the exceptionally easy and precisely identification of unexpanded stents in coronary arteries, which present main mechanical cause for stent thrombosis, after PCI.